1994
DOI: 10.1029/94gl01599
|View full text |Cite
|
Sign up to set email alerts
|

The roles of time and displacement in the evolution effect in rock friction

Abstract: Room temperature friction experiments on quartzo‐feldspathic rocks obey a velocity dependence of strength which consists of two opposite‐sensed effects. The second of these effects has a negative velocity dependence and evolves over a characteristic displacement. This evolution effect was originally attributed by Dieterich [1978; 1979] to an underlying time‐dependent process but is often described by either of two empirical evolution laws. One depends explicitly on displacement (slip law) and the other retains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
419
12

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(457 citation statements)
references
References 8 publications
26
419
12
Order By: Relevance
“…On the other hand, there is strong experimental evidence that frictional surfaces undergo time-dependent healing at zero slip speed [Dieterich and Kilgore, 1994;Beeler et al, 1994], behavior that the slip law cannot accommodate. For this reason the aging law has become the law of choice among modelers over the last decade.…”
Section: What Experiments Showmentioning
confidence: 99%
“…On the other hand, there is strong experimental evidence that frictional surfaces undergo time-dependent healing at zero slip speed [Dieterich and Kilgore, 1994;Beeler et al, 1994], behavior that the slip law cannot accommodate. For this reason the aging law has become the law of choice among modelers over the last decade.…”
Section: What Experiments Showmentioning
confidence: 99%
“…This preparatory phase, during which the frictional resistance increases logarithmically with time [Dieterich, 1972;Beeler et al, 1994;Karner et al, 1997;Karner and Marone, 1998;Marone, 1998], has been interpreted as a result of the time-dependent growth of the real asperity contact area between the two opposite rock walls and between the grain particles comprising gouge materials [Mizoguchi et al, 2009]. The present constitutive model assumes that the fault is already prone to rupture, as for the slip-weakening functions [Ida, 1972;Ionescu and Campillo, 1999].…”
Section: Shape Of the Slip-weakening Curvementioning
confidence: 99%
“…The direct effect is always represented as a positive, purely slip rate dependent process, while recent work has shown that the negative slip rate dependent evolution effect is due to slip superimposed on an underlying time-dependent process [Beeler et al, 1994], as originally suggested by Dieterich [1978Dieterich [ , 1979. An empirical constitutive equation based on the original relations of Dieterich [1979] was developed by Ruina [1983] the "slowness" equation [Ruina, 1983].…”
Section: Constitutive Equationsmentioning
confidence: 99%